Invisible Walls: An Examination of the Legal Strategy of the Restrictive Covenant Cases - Leland B. Ware (Washington University Law Quarterly, 1989)
On May 3, 1948, the Supreme Court issued two decisions in four cases that are now remembered as Shelley v. Kraemer. The conflict which caused the litigation arose from a dramatic population shift that occurred in the early decades of the twentieth century. The great migration of black families from rural areas to urban industrial centers prompted various efforts to establish and maintain racial segregation in housing. After legislated segregation failed, private covenants became the primary vehicle for maintaining segregated housing. The forces against restrictive covenants consisted of black families in search of adequate housing, the NAACP, and the lawyers who served on that organization's legal committee. Charles Hamilton Houston, who served at various times as counsel to the NAACP and was dean of Howard University Law School and the architect of the NAACP's school desegregation strategy, devised the restrictive covenant strategy. The covenant strategy involved an evidentiary demonstration of the relationship of crime and disease to overcrowded conditions in urban ghettoes, and the role of restrictive covenants in the perpetuation of those problems. This strategy, which made the victory in Shelley possible, also had a profound influence on the Supreme Court's attitude toward civil rights litigation. This Article will explore the origin and development of the covenants, and examine urban housing conditions in the 1930s and 1940s. It will review the NAACP's legal strategy and that organization's coordination of the covenant litigation, and it will analyze each of the four cases that eventually reached the Supreme Court.
Keywords: Real covenants; Race discrimination